Numerical investigation of backflow in natural draft chimneys. (2021) - Babin, T.; Ramanathan, S.; Muthukumar, S.; Arun, A.P.; Subbiah, S.
Abstract: Natural draft chimneys are the traditional chimneys, which are being the most used because of its low cost and simple design compared to solar and other smart chimneys. However, the use of traditional chimneys reported the problem of back drafting particularly in colder regions. Utilization of various suction devices such as exhaust fan, vacuum cleaner and dryers lead to the development of negative pressure inside the house, which in turn causes possibilities of back drafting in chimneys. This allows the outside air to get into the house and affects the entire ventilation system. Stack effect of dwellings and other environmental factors such as seasonal temperature and pressure changes are the influential factors for back drafting along with the furnace on and off conditions. A numerical analysis of the flow of motion in the chimney was performed to visualize its behavior under all conditions including back drafting. CFD simulation results shown that the inside pressure gradient and temperature gradient of chimney determine the direction of hot dry air gases because of the variation in density of gas with respect to temperature change. The numerical study can be used to modify the design of vertical chimney duct such that flow can get only accelerated on moving towards the top of the chimney.